Agricultural information needs of Pakistani farmers - Naveed, Muhammad Asif; A. Anwar, Mumtaz (Malaysian Journal of Library and Information Science, 2017)
Naveed, M. A., & Anwar, M. A. (2013). Agricultural information needs of Pakistani farmers. Malaysian Journal of Library & Information Science, Vol.18, no. 3: 13-23. This study aims to identify information needs of 84 Pakistani farmers. The study uses face-to-face structured interviews of men, between the ages of 25 and 65 years, actively participating in farming. Their information needs were centered on: soil preparation, seeds, taking care of crops, harvesting activities, and animal husbandry. They depended mainly on interpersonal relationships in meeting their information needs. The role of mass media and printed materials as sources of information was found to be very low. Lack of timely access, low level of education and language barrier were the main problems that these farmers faced while getting the required information. The findings of this study would be helpful in planning and designing need-based information infrastructure for rural farmers. This will add to the existing literature on the topic and will be of help to researchers in developing countries of Asia and Africa.